2014
DOI: 10.3379/msjmag.1403r004
|View full text |Cite
|
Sign up to set email alerts
|

FDTD Analysis of Polarization Properties and Backscattering Coefficients in Aperture-less SNOM

Abstract: Polarization properties in aperture-less scanning near-field optical microscopy (SNOM) were investigated using the 3D finite-difference time-domain (FDTD) method. We found that scattered light became elliptically polarized with linear or circular-polarized light illumination, and the polarization state of scattered light was preserved. In addition, Jones matrices that express the relationship between incident light and scattered light in terms of the polarization states were successfully obtained. We succeeded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…8. show azimuth angles of SNOM signals measured for the azimuth angle of the incident light of 60°and demodulation frequencies Ω and 2Ω are plotted together with a result obtained by the FDTD simulation [30]. In the case of Ω, the azimuth angles of SNOM signals gradually increased with the angle of the azimuth of the incident light, which agreed with the result by FDTD.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…8. show azimuth angles of SNOM signals measured for the azimuth angle of the incident light of 60°and demodulation frequencies Ω and 2Ω are plotted together with a result obtained by the FDTD simulation [30]. In the case of Ω, the azimuth angles of SNOM signals gradually increased with the angle of the azimuth of the incident light, which agreed with the result by FDTD.…”
Section: Resultssupporting
confidence: 82%
“…From the FDTD simulation, we also found that the a-SNOM system can be described by Jones matrix as described [30],…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The size of our model was 3 × 3 × 3 μm 3 , using 3 × 3 × 3 nm 3 cell. The probe was set with normal to the Cr surface to study fundamental polarization properties of a-SNOM, although there was an inclination of approximately 10° in the actual experiment [ 29 , 30 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…We have developed an aSNOM with a high spatial resolution of 14 nm, (10) and we have found that the polarization state of the scattered light is preserved. (11)(12)(13) In this study, we report on SPP measurement in cross grooves made of Au by aSNOM with a high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%